The investigation of microstructure and mechanical properties of resistance spot welded AISI 316L austenitic stainless steel - Mohammed, H.G. (Elsevier Ltd, 2020)
Today, the resistance spot welding (RSW) has become one of the most deployed welding techniques in different industries, with the bulk of automobile industries deploying it due to the simplicity, automation, and higher process speed. Past studies are a deficit of findings involving the use of 3mm thick sheets. The bulk of the studies focused on the spot welding of 316L with a thickness below 2mm. The lack of studies on resistance spot welding of 316L stainless steel with a thickness of more than 2mm is evidenced. This paper aims to investigate the mechanical and microstructure properties of resistance spot welded 316L stainless steel with 3mm thickness. The effect of constant welding parameters on the weld properties such as weld nugget size, tensile-shear load of welded materials, failure modes, Microhardness, and microstructure of weld nuggets were investigated. The results show that the maximum tensile- shear load was 21.549 KN. The Microhardness of the Fusion Zone (FZ) was 230 HV which was higher than that of both Base Metal (BM) (198.8 HV) and Heat Affect Zone (HAZ) (184 HV) respectively. The optical microscopic images showed phase transformation in the FZ. Â© 2020 Elsevier Ltd. All rights reserved.